The Effect of Problem-Based Learning on the Critical Thinking Skills of Elementary School Students - Darmawati, Yuliana; Mustadi, Ali (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
This study aims to determine: (1) the difference in critical thinking skills between students taught using problem-based learning and expository learning, and (2) the influence of implementing problem-based learning on students' critical thinking skills. This study was quasi-experimental research. The study population consisted only of fifth-grade students from SD Negeri 2 Krikilan. In the experimental group, the learning process took place using the problem-based learning model, while in the control group, it took place in an expository manner. The instruments used were tests that measure students' critical thinking abilities in cognitive aspects and a behavioral scale that measures students' critical thinking abilities in behavioral aspects. The data were then analyzed using: (1) descriptive statistics to describe critical thinking skills and learning outcomes, and (2) inferential statistics using independent sample t-tests and MANOVA to test the research hypotheses at a significance level of 5% (Î± = 0.05). The research findings indicate that: (1) there is a significant difference in students' critical thinking skills between the group taught using problem-based learning and the group taught using expository learning, with a p-value of 0.004, and (2) the implementation of problem-based learning positively and significantly influences students' critical thinking skills, with a significance value of 0.005.